Homecoming eaudiobook - Voigt, Cynthia (Tillerman Family, 2015)
The iconic start to the timeless, Newbery-winning series from Cynthia Voigt is repackaged with a fresh new look. "It's still true." That's the first thing James Tillerman says to his older sister, Dicey, every morning. It's still true that their mother has abandoned the four Tillermans in a mall parking lot somewhere in the middle of Connecticut. It's still true that they have to find their own way to Great-aunt Cilla's house in Bridgeport. It's still true that they need to spend as little as possible on food and seek shelter anywhere that is out of view of the authorities. It's still true that the only way they can hope to all stay together is to just keep moving forward. Deep down, Dicey hopes they can find someone to trust, someone who will take them in and love them. But she's afraid it's just too much to hope for. ... A Time Best YA Book of All Time (2021) National Book Award Finalist ALA Best of the Best Books for Young Adults